Fund managers’ performance: effect of risk tolerance - Mahat, Fauziah; Ali, Noor Azman (Universiti Putra Malaysia Press, 2013)
Risk tolerance is one of the behavioral issues that have becoming an important topic within fund management discipline. Knowledge on risk tolerance has grown substantially in which most of the studies are from developed countries such as Australia and United States. However, studies on the risk tolerance on fund managers’ performance in emerging countries particularly in Asia such as Korea, Japan, China and Malaysia are still lacking. Therefore, this book aims to fill the gap in research concerning fund managers and firm risk tolerance which act as the mediating role on fund performance. This book helps to explain the characteristic of fund managers towards the fund performances. It does so by examining the mediating effect of individual fund managers’ risk tolerance which is measured as level of confidence and level of risk tolerance. Based on quantitative analytical approaches, the theoretical model proposed in this book was tested using secondary data gathered from fund management companies registered under the Securities Commission (SC) of Malaysia.